Evaluation of Tarsus Pigmentation in Chickens Fed with Different Levels of Xanthophyll Pigment: A Practical Application of the CIELab System - Lizana , Rony Riveros; Mendoza, Otto Zea; Perales, Carlos Vilchez (International Journal of Poultry Science, 2020)
Background and Objective: The objective of this study was to evaluate a method to assess dermis pigmentation in broiler chickens in response to xanthophyll pigment inclusion in their feed. Materials and Methods: Ninety-six Cobb 500 birds were distributed in a completely randomized design and fed with different diet treatments, including 0.30, 0.50 and 0.90 g kg–1 of xanthophyll pigment extract from marigold, or a control diet without pigment inclusion. On 42th day, the pigmentation of the dermis was evaluated. For this study, the DSM® colorimetric score and CIELab system were used for comparative evaluations, the luminosity (L), redness (a*) and yellowness (b*) of the tarsus skin were recorded. The data obtained using both methods were subjected to Pearson’s correlation analysis. The CIELab data were subjected to ANOVA, Tukey test was used to compare the treatments mean. The non-parametric data were compared using the Kruskal–Wallis test. The software R was used for statistical analysis. Results: The results showed a higher correlation (p